2021
DOI: 10.29244/jipthp.9.2.79-88
|View full text |Cite
|
Sign up to set email alerts
|

Fisikokimia, Mikrobiologi dan Organoleptik Sosis Daging Sapi dengan Penambahan Tepung Biji Durian (Durio zibethinus Murr)

Abstract: Durian seeds are waste products from durian fruit that have not been utilized properly. Durian seedflour contain high starch as well as tapioca flour, therefore, durian seed flour can be combined withtapioca flour as a filler for sausage dough, in order to reduce production costs of sausage products. Theaim of this study was to analyze the physicochemical, microbiological and organoleptic properties of beefsausage with the addition of 0%, 25% and 50% durian seed flour from a maximum 30% of the flour usedin mak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
1
1
0
1
Order By: Relevance
“…The addition of banana stem flour did not affect the flavour of the chicken meat used. Another study conducted by (Apriantini et al, 2021) using durian seed flour as a substitute for flour in making meatballs gave similar results. They reported that using durian seed flour in making sausages resulted in a sausage aroma that was not durian-scented.…”
Section: Aromasupporting
confidence: 53%
“…The addition of banana stem flour did not affect the flavour of the chicken meat used. Another study conducted by (Apriantini et al, 2021) using durian seed flour as a substitute for flour in making meatballs gave similar results. They reported that using durian seed flour in making sausages resulted in a sausage aroma that was not durian-scented.…”
Section: Aromasupporting
confidence: 53%
“…High moisture content stimulates the growth of microorganisms. This is supported by the opinion of [20] that moisture content significantly determines the shelf life of food products, affecting the physical, chemical, enzymatic, and microbiological properties of food. The addition of TGase enzyme and external protein combinations has proven to further reduce the moisture content of beef sausages.…”
Section: Chemical Quality Of Beef Sausage With the Addition Of Transg...mentioning
confidence: 88%
“…Aroma yang ditimbulkan pada rendang daging sapi berasal dari senyawasenyawa volatil yang terdapat pada daging sapi dan pencampuran bumbu. Bumbu dapat memberikan citarasa dan mampu meningkatkan aroma [3]. Menurut [7] ketumbar memiliki aroma yang khas karena minyak atsirinya yang pekat, kesegaran dan nilai gizinya.…”
Section: A Aromaunclassified